Ionic Liquid-Facilitated Preparation of Lignocellulosic Composites - Brent Tisserat; Erik Larson; David Gray; Nathaniel Dexter; Carl Meunier; Lena Moore; Luke Haverhals (International Journal of Polymer Science)
Lignocellulosic composites (LCs) were prepared by partially dissolving cotton along with steam exploded Aspen wood and burlap fabric reinforcements utilizing an ionic liquid (IL) solvent. Two methods of preparation were employed. In the first method, a controlled amount of IL was added to preassembled dry matrix of cotton and Aspen wood with a burlap weave reinforcement. In the second method, IL solvent, cotton, and Aspen wood were mixed to produce a thick paste matrix that was subsequently pressed into the burlap weave reinforcement. The IL-based solvent was removed via water soaking, and the flexural and tensile properties of the LCs were examined. In this study, the matrix paste method produced a superior LC. Variables such as processing time (IL interaction time) and fabric weaves were found to influence the mechanical properties of the LCs. Although significant process optimization can still be realized, the mechanical properties of several of the LCs fabricated in this study were comparable to injection molded test specimens of neat high density polyethylene or neat polypropylene.